Effects of Water-in-Oil Slow-Release Coagulants Based on Fermented Soybean Whey on Gel Properties of Whole Soybean Flour - YI Hongbo, LI Jun, LI Jiayi, WANG Peng, WANG Shengnan, LIU He (Shipin Kexue)
In this study, ultrafine-pulverized whole soybean flour was reconstituted in boiling water and treated by dynamic high pressure microfluidization after cooling down to ambient temperature. Four fermented soybean wheys were prepared by fermentation with Lactobacillus bulgaricus or Streptococcus thermophilus followed by evaporative concentration or the reverse sequence and used separately to prepare water-in-oil (W/O) slow-release coagulants. The effects of different slow-release coagulants on the gel properties of reconstituted whole soybean flour were investigated. The results showed that the gel with fermented soybean whey obtained by S. thermophilus fermentation followed by concentration had the highest gel strength (24.48 g) and water-holding capacity (91.43%) and exhibited high storage modulus (G’) and yield stress (498.22 Pa) in dynamic rheological test. Moreover, it had strong resistance to deformation and breakage. Encapsulation treatment effectively controlled ion release rates, thereby enabling slow gelation. The development and application of controlled-release coagulants based on fermented soybean whey in the production of whole soybean gel products can effectively address the problem of rough network structures caused by rapid gelation, so the controlled-release coagulants will have broad application prospects.